Increased concentrations of human β-defensins in plasma and bronchoalveolar lavage fluid of patients with diffuse panbronchiolitis. Issue 5 (1st May 2003) - Hiratsuka, T; Mukae, H; Iiboshi, H; Ashitani, J; Nabeshima, K; Minematsu, T; Chino, N; Ihi, T; Kohno, S; Nakazato, M
Abstract : Background: Human β-defensin (HBD)-1 and -2 are antimicrobial peptides present in the respiratory tract. Recent reports have indicated reduced activity of β-defensins in cystic fibrosis, suggesting that β-defensins may play an important role in the pathological process of chronic respiratory tract infection. Diffuse panbronchiolitis (DPB) is a progressive disease characterised by frequent episodes of superimposed infection, typically caused by Pseudomonas aeruginosa . The aim of this study was to elucidate the role of these antimicrobial peptides in this disease. Methods: The concentrations of HBD-1 and HBD-2 in plasma and bronchoalveolar lavage (BAL) fluid from 33 patients with DPB and 30 normal adults were measured by radioimmunoassay. Localisation of HBD-2 was investigated immunohistochemically in an open lung biopsy specimen obtained from a patient with DPB. Results: High concentrations of HBD-1 and HBD-2 were noted in BAL fluid from DPB patients. Increased plasma concentrations of HBD-2, but not HBD-1, were found in patients with DPB compared with control subjects. In patients with DPB the HBD-2 concentration in BAL fluid correlated significantly with the numbers of cells recovered from the BAL fluid (total cells, neutrophils, and lymphocytes) and with the BAL fluid concentration of IL-1β. Synthetic HBD-2, but not HBD-1, had dose dependent bactericidal activity against P aeruginosa . Treatment of 14 patients with macrolides significantly reduced BAL fluid concentrations of HBD-2 but not HBD-1 or plasma concentrations of HBD-1 and HBD-2. Immunohistochemistry of lung tissue showed localisation of HBD-2 in the epithelia of the distal bronchioles. Conclusions: These results indicate that β-defensins, particularly HBD-2, participate in antimicrobial defence in the respiratory tract in DPB, and that the BAL fluid concentration of HBD-2 may be a useful marker of airway inflammation in patients with DPB.